2012
DOI: 10.3363/prb.26.4
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF VANADIUM ION ADDITION ON SINTERING OF ^|^beta;-TRICALCIUM PHOSPHATE BY HOT PRESSING

Abstract: High-density β-tricalcium phosphate (β-TCP) ceramics with a small amount of tri-and pentavalent vanadium ions addition (≦1.0 mol%) were successfully prepared by hot pressing. Tri-and pentavalent vanadium ions were substituted for a Ca ion at the Ca(5) site located in β-TCP crystal structure and for a P ion in the PO 4 group, respectively. The sinterability and mechanical properties of β-TCP doped with vanadium ions (V-β-TCPV) were improved with increasing vanadium ion content. The bending and compressive stren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…It has also been demonstrated that densification can be promoted by hot pressing [12,13], hot isostatic pressing [14,15] and spark plasma sintering [16,17], although the necessary equipment is expensive to purchase and to operate. The present work prepared composite sintered bodies in which nanoparticles were dispersed to generate a secondary phase [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been demonstrated that densification can be promoted by hot pressing [12,13], hot isostatic pressing [14,15] and spark plasma sintering [16,17], although the necessary equipment is expensive to purchase and to operate. The present work prepared composite sintered bodies in which nanoparticles were dispersed to generate a secondary phase [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…However, the incorporation of these transition inhibitors may form a substitution-type solid solution with the oxide of β-TCP, thus suppressing the original solubility of β-TCP and resulting in reduced biosorption. It has also been demonstrated that densification can be promoted by hot pressing [6,7], hot isostatic pressing [8,9] and spark plasma sintering [10], although the necessary equipment is expensive to purchase and to operate. The present work prepared composite sintered bodies in which nanoparticles were dispersed to generate a secondary phase [11].…”
Section: Introductionmentioning
confidence: 99%